Analisis Keterampilan Motorik Halus Anak Usia Dini Melalui Kegiatan Menyalin Tulisan Cerita - Nurhaningtyas Agustin; Akhmad Aji Pradana; Diana Sofiyanti (Institut Agama Islam Nahdlatul Ulama Tuban, 2021)
Childhood is a golden period for education provider, because a great opportunity of human development and growth happened on this period. One of human development happened on this period is soft motor skills. This study purposed for describe pre-school soft motor skill by copying story script activities. The kind of this study are quantitative descriptive study with 100 sample of 4-6 years old pre-school student. Data collected by using copying story script test, observation, and documentations. The instrument used on this study is copying story script test sheet and observation. The result of study analyzed using score percentage to describe how much pre-school soft motor skill by copying story script activities. Result of the study show that pre-school soft motor skill by copying story script activities are 84,00 % with “fine” category, meanwhile the result of observation showed that pre-schooler showing positive effort when performing copying story script activities.